Mechanical Properties of Hemp Fiber-Reinforced Polypropylene Composites for Drone Propeller Guard Application - Witawat Singsang; Thanasak Khamsin; Chayapol Prachumchon; Anurak Rodbumrung; Benjamas Netiworaruksa; Natkrita Prasoetsopha; Ing-orn Sittitanadol (Mechanics of Advanced Composite Structures)
A propeller guard is an instrument that helps to avoid Unmanned Aerial Vehicles (UAVs) or drone damage. Commercially, they are made from an engineering plastic such as Acrylonitrile Butadiene Styrene (ABS). This work aims to introduce the hemp fiber-reinforced polypropylene composites as a new competitive material for propeller guards. In this study, polypropylene was thermally mixed with different ratios of hemp fibers by internal mixing at 190°C. Tensile and impact testing were carried out according to ASTM D638 and ASTM D256, respectively. The results showed that the high contents of hemp fibers can enhance the modulus of their composites. Polypropylene composite with 45 wt.% of hemp fibers obtained the highest modulus at 1169.4 MPa. Also, the impact resistances of these composites were higher while the fiber contents were increased. Furthermore, application in drone propeller guard was executed by SIMCENTER 3D software for proving their propeller protection performance of as-prepared composites. The results indicated that polypropylene and its hemp fibers-reinforced composites could be the materials for this drone propeller guard.